Old and new hostparasitoid associations: parasitism of the invasive fruit fly Bactrocera invadens (Diptera: Tephritidae) and five African fruit fly species by Fopius arisanus, an Asian opiine parasitoid - Mohamed, S.A.; Ekesi, S.; Hanna, R. (2010)
Fopius arisanus (Sonan), a solitary koinobiont endoparasitoid of fruit flies, was introduced for testing and final release against the recently discovered species Bactrocera invadens Drew, Tsuruta and White in Africa. Laboratory experiments were conducted to assess host preference, host acceptability for oviposition, and physiological suitability of B. invadens and five other indigenous tephritid fruit fly species, namely, Ceratitis capitata (Wiedemann) (Diptera: Tephritidae), C. cosyra (Walker), C. rosa Karsch, C. fasciventris (Bezzi), and C. anonae Graham. Females of F. arisanus visited all host egg patches, but showed a stronger preference to eggs of B. invadens, which was also most accepted for oviposition. Successful development of parasitoid progenies varied greatly across hosts, with B. invadens yielding the highest parasitoid progeny and C. fasciventris yielding no F. arisanus progeny. Most of the parasitoid eggs laid in C. rosa and C. fasciventris were encapsulated. Sex ratio was not influenced by host species and it was female biased in all hosts that produced parasitoid progeny. Fopius arisanus was able to establish a new association with C. capitata, C. cosyra and to a lesser extent C. anonae. The results are discussed in the light of the potential use of F. arisanus as a biological control agent of B. invadens.